Can you give me some guidance how to solve the simultaneous equations: |
The substitution method works as follows:
In your case, it is easiest to make y the subject of the second equation:
y = 3x + 6
Now use this expression for y in your first equation:
2x + 4(3x + 6) = 10
Solve this equation for x:
2x + 12x + 24 | = | 10 |
14x + 24 | = | 10 |
14x | = | -14 |
x | = | -1 |
Now use your expression for y to finish the solution:
y | = | 3x + 6 |
y | = | 3(-1) + 6 |
y | = | -3 + 6 |
y | = | 3 |
So the solution to the simultaneous equations is:
x = -1 |